The Effect of Sales Promotion and Perceptions of the Ease of Non-Cash Transactions on Interest in Using Shopeepay - Dina Sarah Syahreza; T Teviana; Haikal Rahman; Herni Rizky (Jurnal Manajemen Industri dan Logistik, 2024)
This research aims to examine how sales promotions and the perceived ease of cashless transactions influence the interest in using ShopeePay. Data collection was conducted through questionnaires, while data analysis included multiple linear regression, hypothesis testing (t-test, F-test, and coefficient of determination), which were previously subjected to validity and reliability tests.The results indicate that both sales promotions and perceived ease have a positive and significant impact on the interest in using ShopeePay. Furthermore, the combination of these two factors also proves to have a positive and significant effect on usage interest. The coefficient of determination test yields a value of 0.635, suggesting that 63.5% of the variation in ShopeePay usage interest can be explained by sales promotions and perceived ease, while the remaining percentage is influenced by factors outside the scope of this study.